Novos desafios à gestão local : limites, avanços e perspectivas nos marcos das políticas habitacionais nos municípios da RMBH a partir do Estatuto da Cidade - Silva, Franklin Bruno da (2013)
The formation of the developmental state in Brazil channeled the efforts and resources of the government in favor of big business ventures and capital accumulation at the expense of social benefits and rights of a large part of the population. This action of the rulers on the one hand, capitalism and framed inaugurated the country among the industrialized nations, on the other, crystallized extreme imbalances in the social field, generating part of the portion of the Brazilian population structural conditions of misery, through insufficient supply and fragmented social policies. After years of Populist Republic and the military dictatorship, the Constitution of 1988 brought a new light on the social issues in Brazil. Three major changes contemplated in the Charter of 1988 generated profound impacts on public management and forms of provision of social services and benefits: democratization, decentralization and universal social rights. However, the urban question, largely due to the special interests involved in this area, got your major advances and changes after 2000. Approved the Statute Law City in 2001, determining the emergence of a new regulatory framework for urban and housing policies. The principal points democratization of the management of cities, the municipal role and social function of property. In 2003, the urban question enters final in the federal government's agenda with the creation of the Ministry of Cities and the Council of Cities. In 2005, another important legislation is approved, the National System for Social Housing, dedicated exclusively to solving the housing problems of the lower classes. Therefore, guidelines, principles and objectives, which generally are the beacons and vectors, which currently indicate and underpin the objectives and procedures adopted for the production of urban policies, in particular the social housing were created. It is, therefore, now that goes for the analyzes of more pragmatic issues, ie the systematic provision of urban policies, the complexity and difficulties become denser. The new regulatory frameworks pose as central agents of change municipalities. However, the assumption is to assume that autonomously provision and management of housing policies, it is necessary, among other variables , significant technical and institutional rigging of municipal governments to meet the demands for housing policies, in accordance with the new standards production and management of these stocks. Thus, with the field cut the municipalities of the Metropolitan Region of Belo Horizonte (BHMA), and, according to the perspective of the new historical institutionalism, this work investigates the possibilities and limits of the municipal building production systems and management housing policies in these municipalities. To this end, we investigated the inflections, the new environment and new regulatory frameworks, as well as political and institutional legacies of national developmental period, analyzing the possibilities and limitations created by these factors for the decentralization of housing policies in the BHMA. In parallel, study the presence of indicators for determining the success of decentralization in these localities. Specifically, technical and institutional factors, potentiating, or mitigate , the decentralization of housing policies .